Corruption risks, management practices, and performance in water service delivery in Kenya and Ghana: an agent-based model - Francesc Bellaubi; Claudia Pahl-Wostl (Ecology and Society, 2017)
Our emphasis is on the management of water service delivery (WSD) and on the institutional dynamics of the actors involved in the various water systems, therefore focusing on the interplay between human society and the environment. Water service delivery in Kenya and Ghana is of low quality and there are weak integrity mechanisms in place, which are prone to corruption. Water service delivery is also characterized by pragmatic and opportunistic management practices. We explore the extent to which corruption and management practices affect the performance of WSD by developing an exploratory agent-based model (ABM) that builds on the principal-agent theory. Based on empirical research from case studies in Kenya and Ghana, the different actors involved in WSD are modeled in terms of principals and agents that play various games reflecting different social dilemmas. Payoffs from the games are defined based on transparency, accountability, participation, and the social costs of the relationship between the principals and the agents. Decisions made by bounded-rational actors take into consideration the expected payoff but also social comparison. The results show that corruption risks and opportunistic practices reduce the performance of WSD. Furthermore, the relevance of the work is the highlighting of the use of social simulation (ABM), built on case studies, to understand these complex relationships in Kenya and Ghana.